Feasibility Analysis of the Development Plan of Air Putih-Selat Baru Road from Traffic Perspectives - Asni Susanti; Faisal Ananda (Politeknik Negeri Batam, 2025)
Along with the development of the population and according to the spatial layout of the Bengkalis Regency, a road plan is needed that can facilitate movement from Bengkalis District to Bantan District. Based on this condition, the Public Works and Spatial Planning Office of Bengkalis Regency plans to build the Air Putih - Selat Baru Poros Road. However, before carrying out the road construction work, it is necessary to assess the feasibility of the planned road construction using one of the study stages, namely a feasibility study. The method used in this study is the with and without method in terms of traffic. In the feasibility analysis from a Traffic point of view, the Degree of Saturation (DJ) indicator is used. After conducting a feasibility analysis, the results show that the degree of saturation of the existing road is still below the standard value (0.85), namely 0.15, so it can be said that it is not feasible in terms of traffic.